PERAN DAN FUNGSI SATUAN POLISI PAMONG PRAJA (SATPOL PP) DALAM PENEGAKAN PERATURAN DAERAH KOTA TANGERANG NOMOR 7 TAHUN 2005 TENTANG PELARANGAN PENGEDARAN DAN PENJUALAN MINUMAN BERALKOHOL - Andreas Dharma Putra Dori; ahmad redi (Jurnal Hukum Adigama, 2022)
Liquor is a drink that contains ethanol, which is a substance if consumed will have an impacton the level of consciousness (drunk). Consuming alcoholic beverages can endanger health,physically and spiritually, disrupt security and public order, and threaten life. In Indonesia, thesale of alcoholic beverages is limited to those who are 21+ years old, their circulation is quitestrict and monitored by the state. However, in the city of Tangerang there are still so many illegalliquor circulations. The problems that arise are about what factors influence the prohibition of thedistribution of alcohol in the city of Tangerang, and what ef orts have been made by the Satpol PPin enforcing the Tangerang City Regulation No. 7/2005 concerning the Prohibition of Distributionand Sales of Alcoholic Beverages. The type of research used is empirical-normative, the researchspecification is descriptive, the data collection technique is primary data with literature studytechniques and secondary data with interview techniques, the type of research approach is thestatutory approach (statue approach), and conceptual approach (conceptual approach). Satpol PPhas taken many actions in enforcing this regional regulation, including; (1) socialization, (2)cooperation with the community, (3) supervision and control, (4) confiscation, and (5)extermination. From the data on alcohol confiscation and destruction for the last 2 years, therewas an increase from 3,140 bottles to 4,837. It is clear that the Tangerang City Satpol PP hascarried out its duties properly and correctly in accordance with the applicable Standard OperatingProcedure.